The combined effect of dental post and cement materials on fracture resistance and fracture mode of endodontically-treated teeth - Mohamed Abdulmunem,; Ali Dabbagh,; Hadijah Abdullah,; Noor Hayaty Abu Kasim, (Universiti Kebangsaan Malaysia, 2015)
The aim of this study was to investigate the simultaneous influence of various dental posts and cementation materials on the fracture resistance and failure mode of the endodontically-treated teeth. Sixty endodontically treated upper central incisors were randomly divided into two main groups, each consisted of three subgroups restored with titanium, fiber and stainless steel posts. The posts in the first and second groups were luted with zinc phosphate and composite resin cements, respectively. Composite cores were built-up over the specimens and then retained with nickel-chromium crowns. Specimens were thermocycled and then loaded at 135o until failures were observed. The obtained data of fracture resistances and failure modes were analyzed using Two-way ANOVA and the Chi-Square tests, respectively. The results showed that the zinc phosphate cement resulted in relatively higher fracture resistances. However, luting of dental posts with composite resin provided more restorable failures in endodontically-treated teeth. Moreover, the teeth restored by fiber posts exhibited desirable fracture resistances with more restorable failure modes, compared with those restored by titanium or stainless steel posts.